Ambiguity Aversion in Engineers. Issue 1 (2nd January 2019) - Brown, Christopher L.; Utley, Dawn R.
Abstract: This article explores whether engineers exhibit the cognitive bias Ambiguity Aversion. Ambiguity Aversion, in which individuals prefer an unambiguous option to an objectively equal or superior ambiguous option, has been previously demonstrated to exist in the general population in decision research. The research presented here was performed by conducting Ambiguity Aversion experiments from prior research in a sample including roughly equivalent numbers of engineers and non-engineers. This research demonstrates that engineers do exhibit Ambiguity Aversion and that they do so to a significantly greater degree than the general population. This finding may have significant implications for both researchers and practitioners.